Evaluation of some botanicals oils for the management of Maize weevil, Sitophilus zeamais Motsch. (Coleoptera: Curculionidae) - Kifle Gebreegziabiher; Mulatu wakgari; Muluken Goftishu (International Journal of Life Sciences, 2017)
The study was conducted at the Plant Protection Laboratory of Haramaya University at a controlled environment of 28±20C and 75±5% R.H. The objectives were to determine the effective doses of neem seed powder, citrus peel powder and their oil extracts and to evaluate some improved varieties and land races of sorghum for their resistance to maize weevil. Treatments were arranged in CRD replicated four times. Fifty unsexed 3-6 days old maize weevil adults were introduced to each glass jar containing 0.1kg muyra-2 seed. In the first botanical study, neem seed and citrus peel oils each at five rates of 0.25, 0.5, 0.75, 1, 1.5 ml, Malathion 5% dust and acetone treated control were evaluated. The results indicated that, all of the parameters analyzed at all rates of the botanical oils showed significant difference over the acetone treated control except for F1 progeny emergence and weight loss at 0.25 ml NSO. The botanical oils at rates of 0.75, 1 and 1.5 ml NSO and 1.5 ml CPO per 100 g sorghum produced adult weevil mortality in the range of 91.25-100% and seed protection of 83-100% similar to that of the positive control. For the same botanical oil rates weevil emergence, seed damage and weight losses were statistically at par with Malathion 5% dust. However sorghum seeds treated with botanical oils showed significant reduction in germination compared to Malathion 5% dust. Further research on the botanical oils for long period of time under farmer’s storage structure could be necessary.